Knowledge-based development from the citizen's perspective: a study from Southern Brazil. (2018) - Nespolo, Daniele; Fachinelli, Ana Cristina; Fortes, Valter Marcos Monteiro; Milan, Gabriel Sperandio; Camargo, Maria Emilia
The objective of this study is to analyse the relation between the personality of cities and the knowledge citizenship in the region of the Associação dos Municípios da Encosta Superior do Nordeste – a Southern Brazil association of municipalities. Personal knowledge-based development identifies and explores the competence of citizens in the development of their ability, as knowledge citizens, to better use community assets aiming local development. This perspective may be directly related to the personality of the cities. A survey was carried-out with a sample population of 504 young citizens. Statistical techniques such as descriptive statistical analyses, confirmatory factor analyses and correlation were used for data analysis. The results indicate the positive correlation between the personality of the cities and the knowledge citizenship among the following dimensions: performance based on political and civil values and attitude of the citizens.